The big bad wolf : a novel - Patterson, James, 1947- (Boston : Little, Brown, 2003)
At the outset of his career with the FBI, Alex Cross is instructed to track down a band of kidnappers who are snatching people and possibly selling them into slavery, a case that is complicated by a terrible threat to Cross's own family.
Accelerated Reader AR
Keywords: Cross, Alex (Fictitious character) -- Fiction; African American psychologists -- Fiction; Government investigators -- Fiction; Forensic psychology -- Fiction; Slave trade -- Fiction; Kidnapping -- Fiction; Washington (D.C.) -- Fiction; Psychological fiction; Mystery fiction